Prevalence of admission plasma glucose in 'diabetes' or 'at risk' ranges in hospital emergencies with no prior diagnosis of diabetes by gender, age and ethnicity. Issue 3 (15th May 2020) - Ghosh, Sandip; Manley, Susan E.; Nightingale, Peter G.; Williams, John A.; Susarla, Radhika; Alonso‐Perez, Irene; Stratton, Irene M.; Gkoutos, Georgios V.; Webber, Jonathan; Luzio, Stephen D.; Hanif, Wasim; Roberts, Graham A.
Abstract: Aims: To establish the prevalence of admission plasma glucose in 'diabetes' and 'at risk' ranges in emergency hospital admissions with no prior diagnosis of diabetes; characteristics of people with hyperglycaemia; and factors influencing glucose measurement. Methods: Electronic patient records for 113 097 hospital admissions over 1 year from 2014 to 2015 included 43 201 emergencies with glucose available for 31 927 (74%) admissions, comprising 22 045 people. Data are presented for 18 965 people with no prior diagnosis of diabetes and glucose available on first attendance. Results: Three quarters (14 214) were White Europeans aged 62 (43‐78) years, median (IQ range); 12% (2241) South Asians 46 (32‐64) years; 9% (1726) Unknown/Other ethnicities 43 (29‐61) years; and 4% (784) Afro‐Caribbeans 49 (33‐63) years, P < .001. Overall, 5% (1003) had glucose in the 'diabetes' range (≥11.1 mmol/L) higher at 8% (175) for South Asians; 16% (3042) were 'at risk' (7.8‐11.0 mmol/L), that is 17% (2379) White Europeans, 15% (338) South Asians, 14% (236) Unknown/Others and 11% (89) Afro‐Caribbeans, P < .001. The prevalence for South Asians aged <30 years was 2.1% and 5.2%, respectively, 2.6% and 8.6% for Afro‐Caribbeans <30 years, and 2.0% and 8.4% for White Europeans <40 years. Glucose increased with age and was more often in the 'diabetes' range for South Asians than White Europeans with South Asian men particularly affected. One third of all emergency admissions were for <24 hours with 58% of these having glucose measured compared to 82% with duration >24 hours. Conclusions: Hyperglycaemia was evident in 21% of adults admitted as an emergency; various aspects related to follow‐up and initial testing, age and ethnicity need to be considered by professional bodies addressing undiagnosed diabetes in hospital admissions. Abstract : Glucose needs to be measured in all adults admitted as an emergency not just those over 40/30 years old, as younger people particularly South Asians and Afro‐Caribbeans are at risk of being admitted with undiagnosed diabetes. Overall, 5% of emergency admissions had glucose in the 'diabetes' range, 8% if South Asian and Afro‐Caribbean, with 16% of people in the 'at risk' range. One third of all emergency admissions were for <24 hours with 58% of these having glucose measured compared to 82% with duration >24 hours.